Combination of cabazitaxel and plicamycin induces cell death in drug resistant B-cell acute lymphoblastic leukemia. (September 2018) - Nair, Rajesh R.; Piktel, Debbie; Geldenhuys, Werner J.; Gibson, Laura F.
Highlights: High-throughput screening identified cabazitaxel and plicamycin for use in ALL. Cabazitaxel and plicamycin show synergism in inducing death in ALL cells. Nanoparticle formulation of cabazitaxel and plicamycin retains their activity. Abstract: Bone marrow microenvironment mediated downregulation of BCL6 is critical for maintaining cell quiescence and modulating therapeutic response in B-cell acute lymphoblastic leukemia (ALL). In the present study, we have performed a high throughput cell death assay using BCL6 knockdown REH ALL cell line to screen a library of FDA-approved oncology drugs. In the process, we have identified a microtubule inhibitor, cabazitaxel (CAB), and a RNA synthesis inhibitor, plicamycin (PLI) as potential anti-leukemic agents. CAB and PLI inhibited cell proliferation in not only the BCL6 knockdown REH cell line, but also six other ALL cell lines. Furthermore, combination of CAB and PLI had a synergistic effect in inhibiting proliferation in a cytarabine-resistant (REH/Ara-C) ALL cell line. Use of nanoparticles for delivery of CAB and PLI demonstrated that the combination was very effective when tested in a co-culture model that mimics the in vivo bone marrow microenvironment that typically supports ALL cell survival and migration into protective niches. Furthermore, exposure to PLI inhibited SOX2 transcription and exposure to CAB inhibited not only Mcl-1 expression but also chemotaxis in ALL cells. Taken together, our study demonstrates the utility of concomitantly targeting different critical regulatory pathways to induce cell death in drug resistant ALL cells.